Iatrogenic subclavian artery puncture repair with Angio-Seal deployment and balloon occlusion - Gąsecka, Aleksandra; Idzik, Aleksandra; Burban, Anna; Pietrasik , Arkadiusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
A central venous catheter (CVC) is used during high-risk operations to prevent hypovolemic shock. Whereas arterial puncture during CVC insertion is quite frequent (2.9%), arterial cannulation is a less common complication (0.2%) [1]. We describe the successful removal of a CVC, inadvertently placed in the subclavian artery, with a collagen-based Angio-Seal closure device (St. Jude Medical, US).